A novel method of identifying damage types in carbon fiber-reinforced plastic cross-ply laminates based on acoustic emission detection using a fiber-optic sensor. (27th October 2016) - Yu, Feng-ming; Okabe, Yoji; Wu, Qi; Shigeta, Naoki
Abstract: We applied a highly sensitive phase-shifted fiber-optic Bragg grating (PS-FBG) sensor with a broad bandwidth to acoustic emission (AE) detection in a composite material. Based on AE detection, this research proposed a novel method to identify damage types in carbon fiber-reinforced plastic (CFRP) laminates. Because the PS-FBG sensor measured pure dynamic strain, the detected AE signals had great physical reliability, which made elastic wave theory suitable for analysis of the signal. The analysis clarified the different characteristics of Lamb wave modes in three types of AEs caused by a transverse crack, delamination and fiber breakage. Additionally, the ratios of the amplitudes of the S0 mode to the A0 mode and the peak frequencies quantitatively evaluated the mode characteristics in the AE signals. Simultaneously using the two physical parameters, we identified the three types of damage among the AE signals detected in a three-point bending test. Furthermore, the finite element method-based AE wave propagation simulation agreed well with the identification results. Hence, the proposed identification method with the PS-FBG sensor has great physical reliability for evaluating damage in composite laminates.